Overexpressing GRE3 in Saccharomyces cerevisiae enables high ethanol production from different lignocellulose hydrolysates - Wang, Haijie; Cao, Limin; Li, Qi; Wijayawardene, Nalin N.; Zhao, Jian; Cheng, Min; Li, Qi-Rui; Li, Xiaobin; Promputtha, Itthayakorn; Kang, Ying-Qian (Frontiers in Microbiology, 2022)
The efficiently renewable bioethanol can help to alleviate energy crisis and environmental pollution. Genetically modified strains for efficient use of xylose and developing lignocellulosic hydrolysates play an essential role in facilitating cellulosic ethanol production. Here we present a promising strain GRE3OE via GRE3 overexpressed in a previously reported Saccharomyces cerevisiae strain WXY70. A comprehensive evaluation of the fermentation level of GRE3OE in alkaline-distilled sweet sorghum bagasse, sorghum straw and xylose mother liquor hydrolysate. Under simulated corn stover hydrolysate, GRE3OE produced 53.39 g/L ethanol within 48 h. GRE3OE produced about 0.498 g/g total sugar in sorghum straw hydrolysate solution. Moreover, GRE3OE consumed more xylose than WXY70 in the high-concentration xylose mother liquor. Taken together, GRE3OE could be a candidate strain for industrial ethanol development, which is due to its remarkable fermentation efficiency during different lignocellulosic hydrolysates.